Nano alpha-aluminum oxide and preparation method thereof

Through the mixing of aluminite powder and ultrapure water and ball milling, combined with jet hedging atomization and ultrasonic calcining technology, high-purity, easy-to-disperse nano-α-alumina powder is prepared, which solves the poor dispersion and poor particle size in the prior art. The problem of uniformity achieves efficient nano-level preparation and is suitable for a variety of materials fields.

CN119284928APending Publication Date: 2025-01-10HUNAN UNIV

Patent Information

Application Number
CN202411453482.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art has problems such as poor dispersion, uneven particle size, high production cost, high energy consumption and environmental pollution when preparing nano-α-alumina, and it is difficult to meet the requirements of high purity and high efficiency at the nano-level.

Method used

By mixing aluminite powder and ultrapure water, standing, ball milling, spraying hedging atomization and ultrasonic high-temperature calcining, high-purity spherical nano-α-oxidation with particle sizes of 100-200 nm is prepared by adding dispersant and seed crystals. Aluminum powder uses a clean environment and high-purity equipment to ensure the purity and dispersion of the product.

Benefits of technology

It realizes nano-level high-purity, easy to disperse, and uniform particle size α-alumina powder, suitable for polishing, ceramics and carrier materials, reducing production costs and energy consumption and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005089809340000011
    Figure HDA0005089809340000011
  • Figure HDA0005089809340000012
    Figure HDA0005089809340000012
Patent Text Reader

Abstract

The invention relates to nano alpha-aluminum oxide and a preparation method thereof, and belongs to the technical field of new materials. The preparation method of the nano alpha-aluminum oxide comprises the following steps: S1, fully mixing aluminum stone powder and ultrapure water, and standing to obtain a pre-solution; s2, a dispersing agent and seed crystals are added into the pre-solution for ball milling, and a mixture is obtained; s3, carrying out jet hedging atomization on the mixture, carrying out spray drying, and calcining to obtain nano alpha-aluminum oxide; the dispersing agent is one or more of polyethylene glycol, polypropylene ketone, dodecyl trimethyl ammonium chloride and octadecyl dimethyl hydroxyethyl ammonium perchlorate. The alpha-aluminum oxide produced by the method is high-purity spherical nanoscale particles which are easy to disperse, the particle size is 100-200nm, the particle size distribution is uniform and concentrated, and the alpha-aluminum oxide is easy to disperse. The prepared nano alpha-alumina powder is easy to process and utilize, and can be directly applied to the fields of polishing materials, additives, ceramic materials, carrier materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to nano alpha-alumina and a preparation method thereof, belonging to the technical field of new materials. Background Art

[0002] Alumina is a widely used chemical inorganic substance with the chemical formula Al2O3. It is a high-hardness compound with a melting point of 2054°C and a boiling point of 2980°C. Currently, there are as many as twelve known crystal forms of alumina, which are allomorphous and heteromorphic. There are three main crystal forms, namely α-alumina, β-alumina and γ-alumina.

[0003] As the most stable crystal form, α-alumina has a very important application and a considerable proportion. α-alumina belongs to the hexagonal closest packing, the Al-O bond is very strong, and it is the most stable high-temperature stable phase of aluminum oxide. It has a series of excellent properties such as high hardness, corrosion resistance, friction resistance and good stability. It is widely used in many fields such as wear-resistant materials, refractory materials, aerospace and semiconductor integrated circuits. Studies have shown that different application fields require different surface morphology, size, dispersibility and physical and chemical properties of α-alumina. In the field of refractory materials, α-alumina is required to have large grains, small shrinkage and strong deformation resistance, and plate-like microcrystals or flakes are preferred. In the fields of 3D printing and electronic materials, microspherical α-alumina is beneficial to improving the fluidity and filling rate of raw materials, thereby improving the thermal conductivity and heat dissipation of products. In the fields of coatings, carriers, and composite materials, spherical α-alumina is widely used because of its regular morphology, small specific surface area, high dispersibility and good sintering characteristics. In the field of diaphragms, high-purity ultrafine α-alumina is beneficial to improving the life of diaphragms and is used to make porous membranes to replace traditional polymer diaphragms. In the field of biomedicine, high-purity nano-spherical alumina is widely used in artificial tooth roots and blood vessels due to its high density and excellent biological inertness. In addition, nano-spherical alumina is also used as raw materials for precision polishing devices, materials and targets.

[0004] At present, the relevant preparation methods generally used for related α-alumina products at home and abroad include: homogeneous precipitation method, drop ball method, aerosol decomposition method, microemulsion method, template method, plasma spray pyrolysis method, sol-gel method, etc.

[0005] CN 113479918 A discloses a method for preparing nano-spherical α-alumina powder; the method is to mix a spherical amorphous alumina precursor and nano-aluminum powder by grinding to obtain a mixture, and then subject the mixture to microwave heating and calcination, the calcination temperature is 950-1030°C, and the insulation time is 60-90 minutes; the microwave hydrothermal method is used to reduce the formation temperature of the precursor, shorten the reaction time, improve the spherical morphology and particle size uniformity of the powder, and obtain a smooth and dense spherical alumina precursor; through microwave calcination technology, rapid and uniform heating is achieved, and the transformation of the spherical morphology to a worm-like structure during the calcination process is reduced; at the same time, the calcination temperature of α-alumina is further reduced by adding nano-aluminum powder seeds during the microwave calcination process, the dispersibility and uniformity of the spherical α-alumina powder are improved, and the production efficiency is improved. However, the invention uses an amorphous alumina precursor and aluminum powder, and requires additional processes to make it, which is costly, and the microwave hydrothermal method and microwave-assisted calcination require relatively high energy consumption.

[0006] CN 104891540 A discloses a method for preparing a micron-sized quasi-spherical α-alumina powder, which comprises the following steps: (1) adding washing water of 1-3 times the weight of aluminum hydroxide, and then adding ammonium bifluoride of 0.5-2‰ of the weight of aluminum hydroxide and ammonium chloride of 0.5-5‰ of the weight of aluminum hydroxide, and stirring to form a mixed solution; the washing water is high-purity water with a temperature not lower than 80°C; (2) the mixed solution is drained to form a filter cake, and then washed, dried, and phase-transformed to form a quasi-spherical α-alumina powder. The quasi-spherical α-alumina prepared by the invention has the advantages of no sharp edges, micron-sized particles, and uniform particle size. However, the prepared micron-sized α-alumina powder has large particles, and its performance in the field of use cannot be comparable to that of nano-sized α-alumina powder.

[0007] CN 103708512 A discloses a method for preparing submicron alumina, and relates to a method for preparing submicron alumina for membrane coating; the steps are: (1) reacting aluminum hydroxide with sodium hydroxide to generate sodium aluminate solution; (2) using a nitric acid solution with an oil mineralizer to perform a neutralization titration reaction; (3) aging, filtering, washing, and drying the precipitated material to obtain pseudo-boehmite; (4) calcining to obtain α-alumina; (5) grinding, screening, and grading to obtain submicron α-alumina. The obtained α-alumina has high conversion rate, high purity, fine particle size, and high dispersion. The D50 of the alumina material is between 200-700nm, and is suitable for lithium battery diaphragm coatings, etc. However, the method uses a strong base of sodium hydroxide and a strong acid of nitric acid, which has high requirements on equipment, causes great pollution to the environment, and has a long neutralization titration reaction period, and is not suitable for mass production.

[0008] CN 106044809 A discloses a method for preparing completely dispersed α-alumina nanoparticles, which adopts α-alumina raw powder obtained by high-temperature calcination of aluminum nitrate as raw material or α-alumina micropowder as raw material, directly grinds the α-alumina micropowder by high-energy ball milling, and the grinding time is 10-100 hours. Then, acid washing is performed with hydrochloric acid or the like, and the ball milling process does not require atmosphere protection. The powder obtained by ball milling is subjected to room temperature acid corrosion to remove impurities from the ball milling tank and the ball milling medium, and high-temperature corrosion of the reactor is not required, so that completely dispersed, non-agglomerated, fine-particle, and 99.56wt% pure α-alumina nanoparticle powder is obtained. However, calcination of nitrate will produce nitrogen oxides such as nitric oxide, which pollutes the environment, the ball milling time is long, the energy consumption is high, and the hydrochloric acid used is too strong, which is corrosive to the environment.

[0009] CN 106044816 A discloses a method for preparing monodisperse nano-α-alumina, wherein a 1-100 nm nano-precursor, nano-γ-alumina, nano-aluminum hydroxide or nano-ammonium aluminum carbonate particles are first dispersed in a potassium sulfate aqueous solution, and octylphenyl polyoxyethylene ether and cyclohexane are mixed in a certain proportion to prepare an oil-in-water type microemulsion, and then the microemulsion is demulsified, centrifuged and dried to obtain nano-particles with a potassium sulfate shell on the surface, and then calcined at 1000-1060° C., washed with water after cooling, and dried to obtain monodisperse nano-α-alumina particles. However, the precursor of the invention is a 1-100 nm nano-material, which is difficult to obtain, and the use of sulfate solution and organic solvent cyclohexane, etc., is prone to produce toxic and harmful substances, and the waste liquid is difficult to treat, which pollutes the environment.

[0010] CN 101200300 A discloses a method for preparing α-alumina powder, which is characterized in that the preparation process is to first heat and dissolve high-purity aluminum salt, add surfactant and surface modifier, then add modified high-purity active carbon black, stir, slowly cool and crystallize to obtain a mixture of carbon black and aluminum salt crystals; then calcine the black mixture in a reducing atmosphere furnace, and calcine it again in an oxidizing atmosphere after calcination to obtain high-activity non-agglomerated α-alumina powder. The method of the present invention uses a two-step calcination technology to calcine aluminum salt in a reducing atmosphere to obtain α-alumina. The obtained α-alumina crystals are surrounded by carbon black, do not agglomerate, have good activity, narrow particle size distribution, and complete crystal shape. Alumina with different shapes between 0.7-15 microns is prepared. However, the invention needs to be calcined in different reducing and oxidizing atmospheres, which has high requirements on equipment; at the same time, micron-level α-alumina is prepared, and the performance difference is large.

[0011] Patent CN101331808 A discloses a process for preparing α-alumina powder for ceramic membrane support. The production process is: after the alumina raw material is screened and impurities are removed, a composite mineralizer is added to mix into an alumina mixture, the alumina mixture is placed in a high-temperature furnace for high-temperature calcination phase transformation, the phase transformation temperature is 1500-1700°C, the heat preservation time is 2-15h, after cooling, corundum balls are added to the ball mill in a ratio of raw material: ball = 1:1-3 for grinding, and then a treatment agent is added for surface treatment, water washing, classification, and drying at 100°C. Prepare spherical α-alumina. However, the calcination temperature of the invention is as high as 1500-1700°C, and the energy consumption requirement is high. Summary of the invention

[0012] The object of the present invention is to provide a nano α-alumina with good dispersibility and small size and a preparation method thereof.

[0013] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0014] A method for preparing nano α-alumina comprises the following steps:

[0015] S1. Fully mix aluminum ore powder and ultrapure water, and let stand to obtain a pre-solution;

[0016] S2, adding a dispersant and seed crystals to the pre-solution and performing ball milling to obtain a mixture;

[0017] S3, spraying and atomizing the mixture, spray drying, and calcining to obtain nano α-alumina;

[0018] The dispersant is one or more of polyethylene glycol, polypropylene ketone, dodecyltrimethylammonium chloride, and octadecyldimethylhydroxyethylammonium perchlorate.

[0019] The stability and uniformity of nano-α-alumina are improved by adding a suitable dispersant.

[0020] In one preferred embodiment, the mass ratio of aluminum ore powder to ultrapure water is 1:20-50, and the preferred mass ratio of aluminum ore to ultrapure water is 1:40-50; the purpose of selecting an excess of ultrapure water is to allow the aluminum ore powder to undergo a precipitation reaction in the solution to generate a precipitate.

[0021] In one preferred embodiment, the aluminum ore powder and ultrapure water are mixed at 50°C to 90°C, preferably 75°C.

[0022] The aluminum ore powder and ultrapure water are mixed at 50℃~90℃ so that the two can be fully and quickly mixed. If the temperature is too low, the reaction will be too slow, and if the temperature is too high, it will cause adhesion between the particles.

[0023] The heating method adopts a clean high and low temperature environment box in the clean room to heat or cool to ensure the cleanliness of the water, thereby ensuring the purity of the materials and products.

[0024] In one preferred embodiment, the mixing time of aluminum stone powder and ultrapure water is 30 minutes to 120 minutes, and preferably the mixing time is 60 minutes. The equipment used in the mixing process is an emulsifier, a dispersing disk disperser or a concentric double-shaft mixer, etc., which is a stirring and mixing equipment with variable frequency controllable stirring speed and cleanness.

[0025] In one preferred embodiment, the standing time is 60 min to 180 min, preferably 80-100 min.

[0026] The environment for static reaction should be a clean room to ensure product purity. The purpose of static reaction is to fully age the mixture, so that the mixed reaction can fully generate precipitates and the precipitated small particles can fully soft-polymerize. The soft polymerization process is conducive to the formation of relatively uniform particles. If the static reaction time is too short, the polymerization is not sufficient, and if the static reaction time is too long, it will lead to large particles and uneven particles.

[0027] In one preferred embodiment, the standing temperature is 25°C to 80°C, preferably 60°C.

[0028] Appropriate temperature can control the rate and intensity of soft agglomeration. If the temperature is too low, soft agglomerates are not easy to form. If the temperature is too high, soft agglomerates are easily broken up, which is not conducive to the homogenization of small particles.

[0029] In one preferred embodiment, the amount of dispersant added is 1%-5% of the weight of the aluminum ore powder; the purpose is to disperse the particles.

[0030] Too much or too little dispersant will affect the dispersibility and viscosity of the solution, and too much dispersant will cause severe adhesion between particles.

[0031] In one preferred embodiment, the amount of seed crystal added is 2-10% by weight of the aluminum ore powder.

[0032] Adding seed crystals can reduce the calcination temperature and promote the crystal growth of particles.

[0033] In one preferred embodiment, the ball milling temperature is 20-90° C., the rotation speed is 100-250 r / min, and the ball milling time is 20-60 min.

[0034] The temperature, speed and time of ball milling all significantly affect the dispersion of particles. If the temperature, speed and ball milling time are too low, the ball milling is insufficient, while if the temperature, speed and ball milling time are too high, secondary agglomeration will occur, which is not conducive to the subsequent spray atomization and spray drying of particle spheroidization.

[0035] In one preferred embodiment, the ball milling temperature is 75° C., the rotation speed is 220 r / min, and the time is 60 min.

[0036] The role of ball milling is to break up and refine the particles of the mixture, disperse the particles evenly on the soft agglomerated precipitate, which is beneficial to the subsequent spray hedge atomization and spray drying particle spheroidization; it is beneficial to the growth of crystal particles during high-temperature calcination, and it is not easy to produce large particles, hard agglomerates and particles of irregular shapes during the growth process. The role of high-temperature ball milling is to promote the dispersion of particles.

[0037] In one preferred embodiment, the total weight ratio of the ball milling beads added in the ball milling to the ball milling raw material is 10:(1-5). Too large or too small a weight ratio of the ball milling beads to the ball milling raw material will affect product performance and efficiency, as well as loss.

[0038] In one preferred embodiment, the ball milling beads are one or more of zirconium beads, aluminum beads, and diamond beads, preferably alumina beads.

[0039] In one preferred embodiment, the size of the ball milling beads is 0.05-0.5 mm, preferably 0.1-0.25 mm and 0.25-0.4 mm. If the ball milling beads are too large, the ball milling effect will not be achieved, resulting in large particles, while if the ball milling beads are too small, the ball milling efficiency will be affected.

[0040] In one of the preferred embodiments, the jet-impact atomization adopts two vertically opposed arranged ejectors, one ejects the turbid liquid after ball milling, and the other ejects a nano-water vapor high-speed jet, wherein the turbid liquid is ejected from top to bottom, and the water vapor is ejected from bottom to top, and the two opposing high-speed jets are ejected to realize the particle atomization and spheroidization of the turbid liquid.

[0041] In one of the preferred embodiments, the aperture of the jet atomization nozzle is 0.5-1.0 mm, the spray pressure range is 0.6-0.8 MPa, and the distance between the nozzles is 80-120 mm.

[0042] In one of the preferred embodiments, the spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 100℃~150℃; the aperture of the nozzle is 0.5~1.0mm; the solid content of the material is 10%~20%; a peristaltic pump is used to extract the sample while stirring; the inlet air temperature is 100℃~150℃; and the peristaltic feed rate is 450-550ml / h.

[0043] In one preferred embodiment, the aluminum stone powder is one or more of high-purity boehmite, pseudo-boehmite, gibbsite, diaspore, boehmite, diaspore and diaspore.

[0044] In one preferred embodiment, the calcination process is: from room temperature to 300°C, the heating rate is 0.5°C ~ 25°C / min; from 300°C to 700°C, the heating rate is 0.5°C ~ 25°C / min; then from 700°C to 1000°C, the heating rate is 0.5°C ~ 25°C / min; insulation, the insulation temperature is 800°C ~ 1000°C, and the insulation time is 20 ~ 260min.

[0045] As the furnace body cools down, composite modified nano-alumina is obtained.

[0046] In one of the preferred embodiments, the container used for calcination is a high purity>99.5% alumina ceramic boat.

[0047] Under the induction of seed crystals, the high temperature of 1000℃ makes the crystal nucleus of the product α-alumina form and grow quickly. The holding time makes its crystal form completely transformed into α-alumina and promotes the stability of α-alumina crystal form. Nano-alumina is obtained by cooling down the furnace body and then cooling down rapidly. The equipment used for calcination is a tubular furnace, and high-temperature calcination with the assistance of ultrasound is conducive to the dispersion of particles.

[0048] In one preferred embodiment, the particle size of the prepared nano α-alumina is 100-200 nm.

[0049] The present invention also claims to protect the nano α-alumina prepared by the above preparation method.

[0050] The present invention is further explained below:

[0051] The invention proposes a method for preparing spherical and easily dispersible nanometer-level high-purity alpha-alumina powder, which mainly uses high-purity aluminum ore as raw material, through precipitation, standing, aging, adding dispersant and seed crystal ball milling, jet atomization and spray drying, and finally adopts ultrasonic high-temperature calcination process. The alpha-alumina powder prepared by the method has the characteristics of particle size of 100-200nm, uniform particle size distribution, high purity, easy dispersion, etc., and is mainly used for polishing materials, additives, ceramic materials, carrier materials, etc., and has good performance.

[0052] The beneficial effects of the present invention are:

[0053] (1) The α-alumina produced by the present invention is a high-purity spherical and easily dispersible nano-scale particle with a particle size of 100-200 nm, uniform and concentrated particle size distribution, and easy dispersion.

[0054] (2) The nano-α-alumina powder prepared by the present invention is easy to process and utilize, and can be directly applied to the fields of polishing materials, additives, ceramic materials, carrier materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The modified and easily dispersible nano α-alumina prepared in Example 1;

[0056] Figure 2 The α-alumina prepared in Comparative Example 1 has poor dispersion effect. DETAILED DESCRIPTION

[0057] The present invention is further described in detail below in conjunction with examples. However, these examples are limited to illustrating the present invention and are not intended to limit the scope of the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.

[0058] Example 1

[0059] 500g of ultrapure water is placed in a beaker, heated to 75°C in an oven, and kept warm; 20g of high-purity boehmite powder is evenly dispersed in ultrapure water, and a stirrer is used to continuously heat, stir and mix for 60min; after stirring and mixing evenly, the temperature is adjusted to 30°C and the mixture is left to stand for 90min; 1500g of 0.1-0.25mm alumina beads are added to a ball mill, and a mixture, 500mg of a dispersant and 800mg of seed crystals are added, and the ball milling time is continued for 60min at a temperature of 45°C and a rotation speed of 220r / min; the ball-milled material is passed through a 100-mesh filter screen; the ball-milled material is then subjected to counter-atomization by a nano-water vapor jet; the aperture of the jet counter-atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jet impact is spray dried at 120°C. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 120°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; a peristaltic pump is used to extract the sample while stirring; the air inlet temperature is 120°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained. After that, the powder is placed in a porcelain boat, and the porcelain boat is placed in a tubular furnace. The heating rate is set as follows: from room temperature to 300°C, heating for 100min; 300-700°C, heating for 40min; 700-950°C, heating for 35min; the insulation temperature is 900°C, and the insulation time is 45min; oxygen is introduced and ultrasonic calcination is assisted. After cooling to room temperature in the furnace, an α-alumina powder with a particle size of about 170nm, obvious particle shaping, and good inter-particle dispersion can be obtained, such as Figure 1 As shown in the figure, the particles of alumina powder with good dispersion are more obvious and have clear boundaries; while the particles of alumina powder with poor dispersion are the opposite, and the particles are still adhered to each other.

[0060] Example 2

[0061] 500g of ultrapure water is placed in a beaker, heated to 50°C in an oven, and kept warm; 25g of high-purity boehmite powder is evenly dispersed in ultrapure water, and heated and stirred for 90 minutes using a stirrer; after stirring and mixing evenly, the temperature is adjusted to 40°C and the mixture is left to stand for 70 minutes; 1500g of 0.1-0.25mm alumina beads are added to a ball mill, and a mixture, 400mg of a dispersant and 1000mg of seed crystals are added, and the ball milling time is continued for 60 minutes at a temperature of 30°C and a rotation speed of 200r / min; the ball-milled material is passed through a 100-mesh filter screen; the ball-milled material is then sprayed with nano-water vapor for counter-atomization; the aperture of the spray counter-atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jet impact is spray dried at 150°C. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 150°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; the sample is extracted by a peristaltic pump while stirring; the air inlet temperature is 150°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained; then the powder is placed in a porcelain boat, and the porcelain boat is placed in a tubular furnace, and the heating rate is set as follows: from room temperature to 300°C, heating for 80min; 300 to 700°C, heating for 35min; 700 to 1050°C, heating for 30min; the insulation temperature is 1000°C, and the insulation time is 60min; oxygen is introduced, and ultrasonic assisted calcination is performed. After cooling in the furnace, an α-alumina powder with a particle size of about 200nm, obvious particle formation, and good inter-particle dispersion can be obtained.

[0062] Example 3

[0063] 500g of ultrapure water is placed in a beaker, heated to 90°C in an oven, and kept warm; 12.5g of high-purity boehmite powder is evenly dispersed in ultrapure water, and heated and stirred for 75min using a stirrer; after stirring and mixing evenly, the temperature is adjusted to 25°C and the mixture is left to stand for 60min; 1500g of 0.1-0.25mm alumina beads are added to a ball mill, and a mixture, 600mg of a dispersant and 1200mg of seed crystals are added, and the ball milling time is continued for 60min at a temperature of 25°C and a rotation speed of 240r / min; the ball-milled material is passed through a 120-mesh filter screen; the ball-milled material is then subjected to counter-atomization with nano-water vapor jet; the aperture of the jet counter-atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jetting is spray dried at 110°C. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; the sample is extracted by a peristaltic pump while stirring; the air inlet temperature is 110°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained; the powder is then placed in a porcelain boat, and the porcelain boat is placed in a tubular furnace, and the heating rate is set as follows: from room temperature to 300°C, heating for 120min; 300 to 700°C, heating for 50min; 700 to 1000°C, heating for 25min; the insulation temperature is 1000°C, and the insulation time is 30min; oxygen is introduced, and ultrasonic assisted calcination is performed. After cooling in the furnace, an α-alumina powder with a particle size of about 150nm, obvious particle formation, good dispersion between particles and relatively uniform distribution can be obtained.

[0064] Comparative Example 1

[0065] 500g of ultrapure water is placed in a beaker, heated to 100°C in an oven, and kept warm; 20g of high-purity boehmite powder is evenly dispersed in ultrapure water, and a stirrer is used to continuously heat, stir and mix for 75min; after stirring and mixing evenly, the temperature is adjusted to 25°C and the mixture is left to stand for 120min; 1500g of 0.1-0.25mm alumina beads are added to a ball mill, and a mixture, 5000mg of a dispersant and 800mg of seed crystals are added, and the ball milling time is continued for 60min at a temperature of 25°C and a rotation speed of 220r / min; the ball-milled material is passed through a 120-mesh filter screen; the ball-milled material is then subjected to counter-atomization by a nano-water vapor jet; the aperture of the jet counter-atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jet impact is spray dried at 110°C. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; a peristaltic pump is used to extract samples while stirring; the air inlet temperature is 110°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained; the powder is then placed in a porcelain boat, and the porcelain boat is placed in a tubular furnace, and the heating rate is set as follows: from room temperature to 300°C, heating for 120min; 300-700°C, heating for 50min; 700-1000°C, heating for 25min; the insulation temperature is 1000°C, and the insulation time is 30min; oxygen is introduced and ultrasonic calcination is assisted. After cooling in the furnace, an alumina powder with unclear particle formation, adhesion, and uneven dispersion effect can be obtained, such as Figure 2 shown.

[0066] Comparative Example 2

[0067] 500g of ultrapure water is placed in a beaker, heated to 80°C in an oven, and kept warm; 20g of high-purity boehmite powder is evenly dispersed in ultrapure water, and a stirrer is used to continuously heat, stir and mix for 75min; after stirring and mixing evenly, the temperature is adjusted to 25°C and the mixture is left to stand for 300min; 1500g of 0.1-0.25mm alumina beads are added to a ball mill, and a mixture, 500mg of a dispersant and 1000mg of seed crystals are added, and the ball milling time is continued for 60min at a temperature of 25°C and a rotation speed of 200r / min; the ball-milled material is passed through a 120-mesh filter screen; the ball-milled material is then subjected to counter-atomization by a nano-water vapor jet; the aperture of the jet counter-atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jetting is spray dried at 110°C, and the spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; the sample is extracted by a peristaltic pump while stirring; the air inlet temperature is 110°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained; then the powder is placed in a porcelain boat, and the porcelain boat is placed in a tubular furnace, and the heating rate is set as follows: from room temperature to 300°C, heating for 120min; 300-700°C, heating for 50min; 700-1000°C, heating for 25min; the insulation temperature is 1000°C, and the insulation time is 30min; oxygen is introduced, and ultrasonic assisted calcination is performed. After cooling in the furnace, an α-alumina powder with unclear particle formation, porous structure, large particles, and uneven dispersion effect can be obtained.

[0068] Comparative Example 3

[0069] 500g of ultrapure water is placed in a beaker, heated to 100°C in an oven, and kept warm; 20g of high-purity boehmite powder is evenly dispersed in ultrapure water, and a stirrer is used to continuously heat, stir and mix for 75min; after stirring and mixing evenly, the temperature is adjusted to 25°C and the mixture is left to stand for 120min; 1500g of 0.1-0.25mm alumina beads are added to a ball mill, and a mixture, 500mg of a dispersant and 800mg of seed crystals are added, and the ball milling time is continued for 180min at a temperature of 25°C and a rotation speed of 200r / min; the ball-milled material is passed through a 120-mesh filter screen; the ball-milled material is then atomized by a counter-jet with nano-water vapor; the aperture of the jet counter-jet atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jetting is spray dried at 110°C. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; a peristaltic pump is used to extract the sample while stirring; the air inlet temperature is 110°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained; the powder is then placed in a porcelain boat, and the porcelain boat is placed in a tube furnace, and the heating rate is set as follows: from room temperature to 300°C, heating for 120min; 300 to 700°C, heating for 50min; 700 to 1000°C, heating for 25min; the insulation temperature is 1000°C, and the insulation time is 30min; oxygen is introduced, and ultrasonic assisted calcination is performed. After cooling in the furnace, α-alumina powder with large particles, interconnected, porous, and uneven dispersion effect can be obtained.

[0070] Comparative Example 4

[0071] 500g of ultrapure water is placed in a beaker, heated to 70°C in an oven, and kept warm; 20g of high-purity boehmite powder is evenly dispersed in ultrapure water, and a stirrer is used to continuously heat, stir and mix for 75min; after stirring and mixing evenly, the temperature is adjusted to 25°C and the mixture is left to stand for 120min; 1500g of 1-1.5mm alumina beads are added to a ball mill, and a mixture, 500mg of a dispersant and 800mg of seed crystals are added, and the ball milling time is continued for 60min at a temperature of 25°C and a rotation speed of 400r / min; the ball-milled material is passed through a 100-mesh filter screen; the ball-milled material is then subjected to counter-atomization by a nano-water vapor jet; the aperture of the jet counter-atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jetting is spray dried at 110°C. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 110°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; the sample is extracted by a peristaltic pump while stirring; the air inlet temperature is 110°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained; the powder is then placed in a porcelain boat, and the porcelain boat is placed in a tube furnace, and the heating rate is set as follows: from room temperature to 300°C, heating for 120min; 300 to 700°C, heating for 50min; 700 to 1000°C, heating for 25min; the insulation temperature is 1000°C, and the insulation time is 30min; oxygen is introduced, and ultrasonic assisted calcination is performed. After cooling in the furnace, large-particle α-alumina powder with a size of micron can be obtained.

[0072] Comparative Example 5

[0073] 500g of ultrapure water is placed in a beaker, heated to 70°C in an oven, and kept warm; 20g of high-purity boehmite powder is evenly dispersed in ultrapure water, and heated and stirred for 75 minutes using a stirrer; after stirring and mixing evenly, the temperature is adjusted to 25°C and the mixture is left to stand for 120 minutes; 1500g of 0.1-0.25mm alumina beads are added to a ball mill, and a mixture, 500mg of a dispersant and 800mg of seed crystals are added, and the ball milling time is continued for 60 minutes at a temperature of 25°C and a rotation speed of 200r / min; the ball-milled material is passed through a 100-mesh filter screen; the ball-milled material is then sprayed with nano-water vapor for counter-atomization; the aperture of the spray counter-atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6-0.8MPa, and the distance between the nozzles is 80-120mm. The material obtained after the jetting is spray dried at 180°C. The spray drying process is as follows: the internal pressure is above 0.5MPa, the temperature of the drying steam is 180°C; the aperture of the nozzle is 1.0mm; the solid content of the material is 20%; the sample is extracted by a peristaltic pump while stirring; the air inlet temperature is 180°C; the peristaltic feed rate is 500ml / h, and a spherical mixture powder is obtained; the powder is then placed in a porcelain boat, and the porcelain boat is placed in a tubular furnace, and the heating rate is set as follows: from room temperature to 300°C, heating for 120min; 300 to 700°C, heating for 50min; 700 to 1000°C, heating for 25min; the insulation temperature is 1000°C, and the insulation time is 30min; oxygen is introduced, and ultrasonic assisted calcination is performed. After cooling with the furnace, α-alumina powder with larger particles, mutual adhesion, and uneven dispersion effect can be obtained.

[0074] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0075] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing nano α-alumina, characterized in that: The following steps are involved: S1. Fully mix aluminum ore powder and ultrapure water, and let stand to obtain a pre-solution; S2, adding a dispersant and seed crystals to the pre-solution and performing ball milling to obtain a mixture; S3, spraying and atomizing the mixture, spray drying, and calcining to obtain nano α-alumina; The dispersant is one or more of polyethylene glycol, polypropylene ketone, dodecyltrimethylammonium chloride, and octadecyldimethylhydroxyethylammonium perchlorate.

2. The preparation method according to claim 1, characterized in that: The mass ratio of aluminum ore powder to ultrapure water is 1:20-50.

3. The preparation method according to claim 2, characterized in that: The aluminum ore powder and ultrapure water are mixed at 50° C. to 90° C.; the mixing time of the aluminum ore powder and ultrapure water is 30 min to 120 min.

4. The preparation method according to claim 1, characterized in that: The standing time is 60 min to 180 min; the standing temperature is 25°C to 80°C.

5. The preparation method according to claim 1, characterized in that: The amount of dispersant added is 1%-5% of the weight of the aluminum ore powder.

6. The preparation method according to claim 1, characterized in that: The amount of seed crystal added is 2-10% of the weight of the aluminum ore powder.

7. The preparation method according to claim 1, characterized in that: The ball milling temperature is 20-90° C., the rotation speed is 100-250 r / min, and the ball milling time is 20-60 min. The total weight ratio of the ball milling beads added to the ball milling raw materials is 10:(1-5).

8. The preparation method according to any one of claims 1 to 7, characterized in that: The aperture of the jet atomization nozzle is 0.5-1.0mm, the spray pressure range is 0.6~0.8MPa, and the distance between the nozzles is 80~120mm; the spray drying process is: the internal pressure is above 0.5MPa, the temperature of the drying steam is 100℃~150℃; the aperture of the nozzle is 0.5~1.0mm; the solid content of the material is 10%~20%; a peristaltic pump is used to extract the sample while stirring; the inlet air temperature is 100℃~150℃; the peristaltic feed rate is 450-550ml / h.

9. The preparation method according to any one of claims 1 to 7, characterized in that: The calcination process is: from room temperature to 300°C, the heating rate is 0.5°C ~ 25°C / min; from 300°C to 700°C, the heating rate is 0.5°C ~ 25°C / min; then from 700°C to 1000°C, the heating rate is 0.5°C ~ 25°C / min; heat preservation, the heat preservation temperature is 800°C ~ 1000°C, and the heat preservation time is 20 ~ 260min.

10. Nano α-alumina prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing alpha-alumina powder

    CN101200300A

  • Circuit arrangement and method for the operation of at least one first and a second lamp

    CN101331808A

  • Preparation method of submicron alumina

    CN103708512A

  • Preparation method of micrometer-scale sphere-like alpha-aluminium oxide powder

    CN104891540A

  • Preparation method of completely-dispersible alpha alumina nanoparticles

    CN106044809A

Cited By

  • Crystal grain controllable alpha-alumina powder and preparation method thereof

    CN120191951A

  • A kind of alpha-alumina powder with controllable grain size and preparation method thereof

    CN120191951B